KAJIAN KINERJA PENYULUH PERTANIAN DI DESA TOROUT KECAMATAN TOMPASO BARU - Sitti Nurlela Mokoginta; Vicky R. B. Moniaga; Melsje Y. Memah (AGRI-SOSIOEKONOMI, 2018)
This study aims to describe the performance of agricultural extension workers in Torout Village, Tompaso Baru Subdistrict. This research was conducted in the village of Torout District of Tompaso Baru for 3 months from May to July 2017 of preparation, data collection through the preparation of research reports. Sampling method is done purposively (purposive), on paddy farmer and corn farmer. The method used in this study using primary and secondary. The method of analysis used in this research is descriptive analysis method. The results showed that the performance of agricultural extension in the Village Torout District of Tompaso Baru with 9 indicators which 6 indicators 3 indicators categorized as high and very high. The success of agricultural extension is a requirement of farmers. Agricultural extension that can be realized if supported by the presence of competent trainers. Agricultural extension are expected to have the ability to carry out complex work, on the basis of professional ability specified, including skills to plan, implement activities, solve problems with responsibilities independently at a certain level, managerial skills and be able to follow the development, knowledge and technologies in the field of expertise .